Морально-психологічний стан населення визволених територій Лівобережної України у 1941–1943 рр. (на основі фондової колекції Національного музею історії Великої Вітчизняної війни 1941–1945 рр.) - Рибченко, Л. (Інститут історії України НАН України, 2008)
The research work is based upon original historical sources: private letters, personal diaries etc. and aims at reconstructing morale and psychological state of various social groups in Left-bank Ukraine under the Nazi occupation as well as their attitude to the restoration of Soviet power and Soviet military mobilizations. Meanwhile the author attempts to cover certain aspects of morale and psychological state of the advancing Red Army servicemen and reinforcements.